Implicaciones sociopolíticas del servicio de agua potable en un territorio de la ciudad de México (2018)
Social representations are visions of the everyday world that historically are constructed together with the diffusion of the media that intensify their audiences. The printed media availability and water policy has not only been reduced to opinions by the press, but also two logics have been grown on the credibility of the information and the truthfulness of it. This study exposes the lines of discussion for the analysis of tandem policies and agenda setting in the availability and supply of water. The results show frames from newspaper audiences are considered promoters of a relative deprivation that is the conformism of the service quality of public water supplies.